2020
DOI: 10.1021/jacs.0c08790
|View full text |Cite
|
Sign up to set email alerts
|

Using DNA to Control the Mechanical Response of Nanoparticle Superlattices

Abstract: Nanoparticle superlattice assembly has been proposed as an ideal means of programming material properties as a function of hierarchical organization of different building blocks. While many investigations have focused on electromagnetic, optical, and transport behaviors, nanoscale self-assembly via supramolecular interactions is also a potentially desirable method to program material mechanical behavior, as it allows the strength and three-dimensional organization of chemical bonds to be used as handles to man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 33 publications
0
26
0
Order By: Relevance
“…Elasticity and hardness reflected the mechanical performance, which depended on the surface ligand of superlattice. Macfarlane’s group used DNA-grafted superlattice assembly to investigate the material mechanical behavior [ 82 ]. Due to the tunability of DNA via specific nuclease pairing, the modulus of superlattice could be tuned nearly two orders of magnitude.…”
Section: Properties Of Dna-grafted 3d Lattice and Their Future Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Elasticity and hardness reflected the mechanical performance, which depended on the surface ligand of superlattice. Macfarlane’s group used DNA-grafted superlattice assembly to investigate the material mechanical behavior [ 82 ]. Due to the tunability of DNA via specific nuclease pairing, the modulus of superlattice could be tuned nearly two orders of magnitude.…”
Section: Properties Of Dna-grafted 3d Lattice and Their Future Applicationmentioning
confidence: 99%
“…Surface stabilizer-mediated compositionally heterogeneous nanocrystal superlattice with catalytic property have been reported [ 83 , 84 ]. For instance, binary Pt-Pd superlattice Au/Fe 3 O 4 superlattice after postprocessing could catalyze the reduction of oxygen to water [ 82 ] and oxidation of carbon monoxide [ 84 ] at a faster rate than the homogeneous nanocrystal. Though the catalysis function of DNA-grafted superlatticehas not been employed to date, the catalytic application of DNA-grated superlattice will not be far.…”
Section: Properties Of Dna-grafted 3d Lattice and Their Future Applicationmentioning
confidence: 99%
“…Mechanical Properties of NPSLs. Because there are multiple methods and ligand interactions that can be used to govern their assembly, different NPSLs have been found to exhibit a wide range of mechanical properties depending on their composition and processing conditions: 130 Young's moduli can range from 100 kPa for hydrated PAE lattices, 131 to 100 MPa for dried hydrogen-bonded polymer-grafted nanoparticles, 65 to 64 GPa for dried NPSLs with cross-linked molecular ligands. 132 In general, however, the mechanical properties of most NPSLs to date have been determined to be comparable to that of glassy polymers, with Young's moduli between 1−10 GPa and hardness on the order of 100 MPa.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In recent years, DNA-linked 3D superlattices composed of metallic NPs have been investigated. 33,35,37,39,[42][43][44][45] In their pioneering work, Mirkin and Schatz have shown that such 3D supercrystals exhibit strong novel optical behaviours resulting from the coexistence of plasmonic and photonic modes. 28,35,46,47 By continuously varying the NPs orientation, periodicity, spacing, size, and shape, as well as the crystal habit, an enormous set of fundamentally interesting metamaterials can be designed.…”
Section: A Introductionmentioning
confidence: 99%